2004
DOI: 10.1262/jrd.50.47
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Functions of Mitogen-activated Protein Kinases and Protein Tyrosine Phosphatases in Ovarian Granulosa Cells

Abstract: Abstract.A number of endocrine and paracrine factors regulate the follicular growth and atresia, which are closely associated with granulosa cell survival and apoptosis. However, the molecular mechanisms underlying the intracellular events induced by these factors are poorly understood. Here, we describe the correlation of mitogen-activated protein kinase (MAPK) activities with granulosa cell survival and apoptosis, and the cellular functions of protein tyrosine phosphatases (PTPs) in these cells based on our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…4). Effect of pharmacological activators or blockers of PKs showed, that PKA, PKG, MAPKs, PI3K/Akt, CDKs, TKs, and ALK can both promote (in some cases also suppress) ovarian granulosa cell proliferation (Makarevich et al, , 2004bTamura et al, 2004;Sirotkin andGrossmann, 2003, 2006;Wang and Tsang, 2007), although the ability of TK-dependent intracellular signaling to stimulate ovarian folliculogenesis and ovulation is reported too (Matousek et al, 1999). The cAMP/PKAdependent intracellular mechanisms can either inhibit (Peluso, 2006;Graves and Lawrence, 1996;Hsueh et al, 1996;Hillier and Tetsuka, 1997), stimulate (Cheadle et al, 2008;Viegas et al, 2008) or not influence (Dupont et al, 2008) follicular cell proliferation, but other PKs are involved predominantly in promotion of ovarian cell cycle.…”
Section: Protein Kinases Control Ovarian Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Effect of pharmacological activators or blockers of PKs showed, that PKA, PKG, MAPKs, PI3K/Akt, CDKs, TKs, and ALK can both promote (in some cases also suppress) ovarian granulosa cell proliferation (Makarevich et al, , 2004bTamura et al, 2004;Sirotkin andGrossmann, 2003, 2006;Wang and Tsang, 2007), although the ability of TK-dependent intracellular signaling to stimulate ovarian folliculogenesis and ovulation is reported too (Matousek et al, 1999). The cAMP/PKAdependent intracellular mechanisms can either inhibit (Peluso, 2006;Graves and Lawrence, 1996;Hsueh et al, 1996;Hillier and Tetsuka, 1997), stimulate (Cheadle et al, 2008;Viegas et al, 2008) or not influence (Dupont et al, 2008) follicular cell proliferation, but other PKs are involved predominantly in promotion of ovarian cell cycle.…”
Section: Protein Kinases Control Ovarian Cell Proliferationmentioning
confidence: 99%
“…Regulators of PKA, PKG, MAPKs, PI3K, Akt, CDKs, TKs, and ALK affecting ovarian follicular cell proliferation (Peluso, 2006;Graves and Lawrence, 1996;Hsueh et al, 1996;Hillier and Tetsuka, 1997;Matousek et al, 1999;Makarevich et al, 2002Makarevich et al, , 2004bTamura et al, 2004;Sirotkin andGrossmann, 2003, 2006;Wang and Tsang, 2007;Dupont et al, 2008;Cheadle et al, 2008;Viegas et al, 2008) can be used for stimulation of ovarian folliculogenesis, increase in number of ovulations and, perhaps, for control of hypogonadism, PCOS and other ovarian disorders associated with impaired follicular growth.…”
Section: Interrelationships Between Different Protein Kinases In the mentioning
confidence: 99%
“…Nonetheless, many reports have indicated the MAPK pathway as a good mediator of the cellular survival in granulosa cells (Tamura et al, 2004). Thyroid hormones have been related to both the MAPK and the PI3K pathways.…”
Section: T 3 and The Pi3k Pathwaymentioning
confidence: 99%
“…However, this activation did not occur with PRL but only in response to S179D PRL, a molecular mimic of the phosphorylated form of PRL. Activation of ERK1/2 by PRL/PRL-RS may be unique to The MAPK family has a central role in various cellular responses including cell proliferation, differentiation, survival, and apoptosis (42,43). Recently, it was shown that MAPK critically regulate the fate of ovarian granulosa cells (25,42).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2 by PRL/PRL-RS may be unique to The MAPK family has a central role in various cellular responses including cell proliferation, differentiation, survival, and apoptosis (42,43). Recently, it was shown that MAPK critically regulate the fate of ovarian granulosa cells (25,42). Activation of p38 MAPK by FSH leads to phosphorylation of HSP-27 in granulosa cells, resulting in cell rounding and aggregation promoting microfilament reorganization and stabilization (44), suggesting a role in granulosa cell survival.…”
Section: Discussionmentioning
confidence: 99%